2022
DOI: 10.3389/fonc.2022.835389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Event-Free Survival Surrogating Overall Survival as the Endpoint in Neoadjuvant Clinical Trials of Gastroesophageal Adenocarcinoma

Abstract: BackgroundGastric cancer (GC) is one of the most common malignant cancers worldwide. The development of potential antitumor agents is being investigated and stimulates more clinical trials. Overall survival (OS) is consistently considered the primary endpoint for clinical trials on treatment effect assessment. However, finding an appropriate endpoint more sensitive and easy for trials is vital. For adjuvant chemotherapy, current evidence has shown that disease-free survival (DFS) could be a surrogate endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…As far as we know, this was the first study to identify PFS-based endpoints systematically in advanced ESCC patients receiving immunotherapy in combination with chemotherapy as 1-L treatment. Previous studies have shown that three-year PFS is a reliable SE of 5-year OS in locally advanced ESCC treated with definitive RT; when treating resectable ESCC and esophageal adenocarcinoma (EAC) and gastroesophageal junction (GEJ) cancer, HR PFS can be used in neoadjuvant, perioperative, or adjuvant settings as a substitute for HR OS ; in addition, in neoadjuvant RCTs of gastric carcinoma(GC) and GEJ adenocarcinoma, event-free survival (EFS) could serve as a SE [ 35 37 ]. However, in the immune-oncology (IO) era, due to the special response patterns of Immuno-checkpoint inhibitors (ICIs) such as pseudoprogression and delayed response, whether the traditional SE for OS is applicable to IO trials is controversial [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this was the first study to identify PFS-based endpoints systematically in advanced ESCC patients receiving immunotherapy in combination with chemotherapy as 1-L treatment. Previous studies have shown that three-year PFS is a reliable SE of 5-year OS in locally advanced ESCC treated with definitive RT; when treating resectable ESCC and esophageal adenocarcinoma (EAC) and gastroesophageal junction (GEJ) cancer, HR PFS can be used in neoadjuvant, perioperative, or adjuvant settings as a substitute for HR OS ; in addition, in neoadjuvant RCTs of gastric carcinoma(GC) and GEJ adenocarcinoma, event-free survival (EFS) could serve as a SE [ 35 37 ]. However, in the immune-oncology (IO) era, due to the special response patterns of Immuno-checkpoint inhibitors (ICIs) such as pseudoprogression and delayed response, whether the traditional SE for OS is applicable to IO trials is controversial [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surrogacy of EFS for OS has been demonstrated in multiple other tumor types, including gastroesophageal cancer, breast cancer, and hematologic malignancies. [35][36][37][38] Despite the lack of proven surrogacy, EFS can provide useful information regarding treatment tolerability and toxicity which is not encapsulated by OS. Given its ease of measurement and earlier maturity compared to OS, we advocate for EFS' use in neoadjuvant clinical trials.…”
Section: Introductionmentioning
confidence: 99%